KARAKTERISTIK ARUS DAN POTENSIAL KATODIK PADA PERLINDUNGAN SISTEM ARUS TERPASANG TERHADAP STAINLESS STEEL TYPE 304 DI LINGKUNGAN AIR LAUT - Asmara, Yuli Panca (Jurnal Kimia (Journal of Chemistry), 2012)
Cathodic protection basically reduces the corrosion rate of a metallic structure by reducing its corrosion potential, bringing the metal closer to an immune state. So, to optimallize the protection, not only potential but also environment and system should be considered in designing cathodic protection. The changes of current provided by a direct current (DC) source should be a counted during the protection. The objective of this laboratory was to studed the polarization behaviour concerning 304 stainless steel immersed in the artificial sweater based on ASTM D 1141 using potentiostat. This task was performed by recording data points (potential across a constant resistor) within a determined potential. Then, the surface morphology of specimen caused by polarisation potential was investigated using an optical microscope and SEM analysis. The current derived from the polarisation diagram by the determination of several points protection potential ranging from -730mV to -1100 mV tend to decrease. The sharp decrease of current occured at protection potential of -1100 mV (from 580 mA/m2to 450 mA/m2) there was a slight decrease at protection potential of -730 mV. The decrease occurred was from 190 mA/m2 to 150 mA/m2. Potential of protection cathodic also influenced the free corrosion potential. At the protection potential of -730 mV, free corrosion potential was -225 mV, and was -450 mV at the protection potential of -1100mV. By visual examination it can be deduced that the decrease of current density occurred was caused by the growth of salt calcareous deposits. By SEM investigation it was indicated that the deposit was made of calcium and magnesium as a result of the increase of pH during protection. The more detail analisys showed that this deposit created local pitting corrosion and decreased pitting potential by 200 mV.
Keywords: Cathodic potential, the changes of current, sainless steel, artificial sweater